Application of photoelectrochemical oxidation of wastewater used in the cooling tower water and its influence on microbial corrosion - Kokilaramani, Seenivasan; Satheeshkumar, Alagersamy; Nandini, M. S.; Narenkumar, Jayaraman; AlSalhi, Mohamad S.; Devanesan, Sandhanasamy; Natarajan, Prabhu Manickam; Rajamohan, Rajaram; Rajasekar, Aruliah; Malik, Tabarak (Frontiers in Microbiology, 2024)
Background Cooling towers are specialized heat exchanger devices in which air and water interact closely to cool the water's temperature. However, the cooling water contains organic nutrients that can cause microbial corrosion (MC) on the metal surfaces of the tower. This research explores the combined wastewater treatment approach using electrochemical-oxidation (EO), photo-oxidation (PO), and photoelectrochemical oxidation (PEO) to contain pollutants and prevent MC. Methods The study employed electro-oxidation, a process involving direct current (DC) power supply, to degrade wastewater. MC studies were conducted using weight loss assessments, scanning electron microscopy (SEM), and x-ray diffraction (XRD). Results After wastewater is subjected to electro-oxidation for 4 h, a notable decrease in pollutants was observed, with degradation efficiencies of 71, 75, and 96%, respectively. In the wastewater treated by PEO, microbial growth is restricted as the chemical oxygen demand decreases. Discussion A metagenomics study revealed that bacteria present in the cooling tower water consists of 12% of Nitrospira genus and 22% of Fusobacterium genus. Conclusively, PEO serves as an effective method for treating wastewater, inhibiting microbial growth, degrading pollutants, and protecting metal from biocorrosion.